The Correlation between Social Support and Depression in Female Student of 12th Class Al Islam 1 Senior High School Surakarta - VICIANITA PUTRI UTAMI; MOHAMMAD FANANI .; SITI AISYAH . (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2015)
Background: The incidence of depression in adolescents can be very dangerous because it can affect learning in the school. To neutralize the incidence of depression in adolescents, we can apply good social support from family, friends, and the environment so the teenager can pass it well. The purpose of this study was to determine the correlation between social support and depression in female student of 12th class Al Islam 1 Senior High School Surakarta. Methods: This study is an observational study with cross sectional analytical conducted in July 2014 in Al Islam 1 Senior High School Surakarta. Sampling is conducted for all of the female students of 12th class, and then exclude sample that cant be inclution and exclution criteria. Correspondent filling: (1) the contents of personal data; (2) L-MMPI questionnaire; (3) ISEL questionnaire to assess the social support scores; (4) BDI Questionnaire to assess depression scores. The data were obtained for 143 students and were analyzed using Spearman through 21.00 SPSS for Windows. Results: The analysis showed Spearman correlation coefficient -0.880; p = 0.000. The strength of the correlation values ??included in the category of very strong (r = 0.8-1.00). p > 0.05 it can be concluded that H1 is accepted and Ho is rejected or suggest a correlation between social support and depression in female student of 12th Class Al Islam 1 Senior High School Surakarta. It also showed the negative direction of correlation. It means that the higher of social support, then lower the depression, and the lower of social support, then higher the depression. Conclusions: There is correlation between social support and depression in female students of 12th class Al-Islam 1 Senior High School Surakarta. The correlation is very strong with the negative direction of correlation means that the higher of social support, then lower the depression, and the lower of social support, then higher the depression. Keywords: Adolescence, social support, depression